High-resolution insertion-site analysis by linear amplification-mediated PCR (LAM-PCR) - Schmidt, M.; Schwarzwaelder, K.; Bartholomae, C.; Zaoui, K.; Ball, C.; Pilz, I.; Braun, S.; Braun, S.; Von Kalle, C.
Integrating vector systems used in clinical gene therapy have proven their therapeutic potential in the long-term correction of immunodeficiencies. The integration loci of such vectors in the cellular genome represent a molecular marker unique for each transduced cell and its clonal progeny. To gain insight into the physiology of gene-modified hematopoietic repopulation and vector-related influences on clonal contributions, we have previously introduced a technology-linear amplification-mediated (LAM)PCR-for detecting and sequencing unknown DNA flanking sequences down to the single cell level (Supplementary Note online). LAM-PCR analyses have enabled qualitative and quantitative measurements of the clonal kinetics of hematopoietic regeneration in gene transfer studies, and uncovered the clonal derivation of non-leukemogenic and leukemogenic insertional side effects in preclinical and clinical gene therapy studies. The reliability and robustness of this method results from the initial preamplification of the vector-genome junctions preceding nontarget DNA removal via magnetic selection. Subsequent steps are carried out on a semisolid streptavidin phase, including synthesis of double complementary strands, restriction digest, ligation of a linker cassette onto the genomic end of the fragment and exponential PCR(s)with vector- and linker cassette-specific primers. LAM-PCR can be adjusted to all unknown DNA sequences adjacent to a known DNA sequence. Here we describe the use of LAM-PCR analyses to identify 5' long terminal repeat (LTR)retroviral vector adjacent genomic sequences (Fig. 1 and Box 1).
Keywords: DNA; MOLECULAR MARKER; RETROVIRUS VECTOR; STREPTAVIDIN